Evidence quality assessment of acupuncture intervention for stroke hemiplegia: an overview of systematic reviews and meta-analyses - Fan, Maoxia; Zhang, Bo; Chen, Chen; Li, Runmin; Gao, Wulin (Frontiers in Neurology, 2024)
Objective:Summarize the conclusions of the systematic review/meta-analysis of the clinical efficacy of acupuncture for stroke hemiplegia, and evaluate its methodological quality and the quality of evidence. Methods: Two researchers searched and extracted 8 databases for systematic reviews (SRs)/meta-analyses (MAs),and independently assessed the methodological quality, risk of bias, reporting quality, and quality of evidence of SRs/MAs included in randomised controlled trials (RCTs).Tools used included the Assessment of Multiple Systematic Reviews 2 (AMSTAR-2), the Risk of Bias in Systematic (ROBIS) scale, the list of Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system.The search time is from database building to July 2023. Results: A total of 11 SRs/MAs were included, including 2 English literature and 9 Chinese literature, with all study sites in China.AMSTAR-2 evaluation results showed that the methodological quality of 11 articles was rated as very low quality; Based on the ROBIS evaluation results, the SRs/MAs was assessed as a high risk of bias; According to the results of the PRISMA checklist evaluation, most of the SRs/MAs reports are relatively complete;According to GRADE system, 42 outcomes were extracted from the included SRs/MAs for evaluation, of which 1 was rated as high-quality evidence, 14 as moderate-quality evidence,14 as low-quality evidence, and 13 as very low-quality evidence.The available evidence indicates that acupuncture has certain clinical efficacy in the treatment of stroke hemiplegia.However, there are still some limitations to this study, such as the lower quality of SRs/MAs methodologies and evidence included, and more high-quality studies are needed to verify them.